2018
DOI: 10.1016/j.foreco.2018.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Fast-growing Larix kaempferi suffers under nutrient imbalance caused by phosphorus fertilization in larch plantation soil

Abstract: There are significant differences in the morphological and physiological responses of larch species with contrasting growth rates under fertilization. However, little is known about species-specific differences in responses to nutrient imbalance caused by fertilization. Therefore, in this study, the effects of nitrogen (N) and phosphorus (P) fertilization on the morphological, physiological and chloroplast ultrastructural traits of two contrasting larch species, fast-growing Larix kaempferi and slowly-growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 121 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…In larch, a rapidly growing genotype is less tolerant to unbalanced nutritional conditions than a slow-growing genotype [66]. However, our research results showed that the tolerance of WC to nutrient deficiency was greater than DL, which resulted in a greater growth rate of WC than DL.…”
Section: Relationship Between the Growth Rate And Tolerance To N-and P-for F Mandshuricamentioning
confidence: 61%
“…In larch, a rapidly growing genotype is less tolerant to unbalanced nutritional conditions than a slow-growing genotype [66]. However, our research results showed that the tolerance of WC to nutrient deficiency was greater than DL, which resulted in a greater growth rate of WC than DL.…”
Section: Relationship Between the Growth Rate And Tolerance To N-and P-for F Mandshuricamentioning
confidence: 61%
“…In addition, the A. colubrina individuals in this study are very young, not to mention that competition for water and nutrients is lower because of the homogeneous spacing. This fact led to younger plants having great potential to extract and recycle nutrients, because plants require more nutrients to form biomass during growth (LI et al, 2018).…”
Section: Nutrition Assessmentmentioning
confidence: 99%
“…Carr] is an ectomycorrhizal coniferous tree species widely distributed in Northeast Asia and planted in wide forested areas of Japan (Fuchen et al 1998;Ryu et al 2009). However, this fastgrowing species is also susceptible to diseases (Ryu et al 2009) and sensitive to O 3 (Wang et al 2015;Agathokleous et al 2017;Sugai et al 2018;) and other stresses (Li et al 2018b;Wang et al 2018). Soil fertilization also changes the symbiosis between Japanese larch roots and ECM (Wang et al 2018) as does elevated O 3 for a hybrid larch (L. gmelinii var.…”
Section: Introductionmentioning
confidence: 99%